Diagnosis and management of intralabyrinthine schwannoma: case series and review of the literature - Di Lullo, Antonella Miriam; Paolucci, Aldo; Motta, Sergio; Cantone, Elena; Barbieri, Emiliano; Cicala, Domenico; Grassi, Roberta; Bruno, Federico; Splendiani, Alessandra; Tortora, Fabio; Cavaliere, Michele; Brunese, Luca (Acta Biomedica Atenei Parmensis, 2020)
Intralabyrinthine schwannoma (ILS) is a rare benign tumor affecting cochlear and vestibular nerves, whose symptoms are generally unspecific and frequently responsible for a late diagnosis. Radiological examinations, with particular reference to magnetic resonance imaging (MRI), represent the only diagnostic technique to identify ILS. On computed tomography ILS can only be indirectly suspected by the presence of surrounding bone remodeling, whereas MRI provides direct visualization of the neoplasm as a filling defect within the labyrinth with vivid contrast enhancement. At the same time, MRI is also helpful in defining ILS anatomical extension into adjacent structures and in planning therapeutic management. Here we report three representative cases of ILS with new pictorial imaging features to improve ILS early detection and optimize subsequent therapeutic management.